2019
DOI: 10.1038/s41598-019-53559-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastric acid inhibitor aggravates indomethacin-induced small intestinal injury via reducing Lactobacillus johnsonii

Abstract: Proton pump inhibitors (PPIs) alter the composition of the intestinal microbiome, exacerbating indomethacin (IND)-induced small intestinal damage. Vonoprazan fumarate inhibits gastric acid secretion using a different mechanism from PPIs. We investigated the effects of both drugs on the intestinal microbiome and IND-induced small intestinal damage. We sought to clarify whether PPI-induced dysbiosis and worsening of the damage were due to a specific drug class effect of PPIs. Rabeprazole administration increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 33 publications
2
36
1
1
Order By: Relevance
“…Indomethacin use may not reproduce identical mechanisms involved in EED etiology but enabled to display many EED features while LPS did not. Experimental models of enteropathy induced by chemical agents such as indomethacin are used in the analysis of pathological mechanisms of enteropathy 29,42 as well as the development of therapeutic agents 43 . Although NSAID-induced enteropathy models do not have the complexity of human EED, the present model can contribute to the study of the disease such as microbiota changes 29 or to the evaluation of nutritional intervention 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin use may not reproduce identical mechanisms involved in EED etiology but enabled to display many EED features while LPS did not. Experimental models of enteropathy induced by chemical agents such as indomethacin are used in the analysis of pathological mechanisms of enteropathy 29,42 as well as the development of therapeutic agents 43 . Although NSAID-induced enteropathy models do not have the complexity of human EED, the present model can contribute to the study of the disease such as microbiota changes 29 or to the evaluation of nutritional intervention 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, complications of excessive gastric acid suppression, like dyspepsia, luminal dysbiosis, gastric microfloral imbalance, vitamin B12 deficiency, pernicious anemia, osteoarthritis, malabsorption of certain drugs active in the acidic microenvironment and even gastric parietal cell hyperplasia and gastric cancer staunchly warrant against rampant use of PPIs and histamine receptor blockers [104]. In fact, a recent study also indicated that PPIs can actually exacerbate indomethacin-induced small intestinal damage by detrimentally altering intestinal microbiome composition [135]. Hence, gastric acid is in no way a physiological evil and opting for antioxidant-based therapeutic strategy to prevent the gastric mucosa from NSAID-induced cytopathies is a rather safer approach than indiscriminate usage of acid suppressors.…”
Section: Risk To the Gastric Mucosal And Small Bowel Injuriesmentioning
confidence: 99%
“…Vonoprazan, which belongs to a class of acid-inhibitory agents called potassium-competitive acid blockers, was approved in Japan in February 2015, and its superiority or non-inferiority to PPIs for the treatment of acid-related diseases has been demonstrated [45][46][47]. Although vonoprazan suppresses gastric acid secretion by a different mechanism from PPIs, a recent animal study reported that both rabeprazole and vonoprazan aggravated NSAIDs-induced small intestinal injury in mice by reducing the population of Lactobacillus johnsonii in the small intestine [48]. Thus, strong inhibitors of gastric acid secretion may commonly cause small intestinal dysbiosis and the resultant aggravation of NSAIDs-induced enteropathy.…”
Section: Risk Factors For Nsaids-induced Enteropathymentioning
confidence: 99%